EGFR Mutation and 11q13 Amplification Are Potential Predictive Biomarkers for Immunotherapy in Head and Neck Squamous Cell Carcinoma - Dou, Shengjin; Zhang, Lin; Wang, Chong; Yao, Yanli; Jiang, Wen; Ye, Lulu; Li, Jiang; Wu, Sicheng; Sun, Debin; Gong, Xiaoli; Li, Rongrong; Zhu, Guopei (Frontiers in Immunology, 2022)
Background: Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignant cancers. The treatment of HNSCC remains challenging despite recent progress in targeted therapies and immunotherapy. Research on predictive biomarkers in clinical settings is urgently needed. Methods: Next-generation sequencing analysis was performed on tumor samples from 121 patients with recurrent or metastatic HNSCC underwent sequencing analysis. Clinicopathological information was collected, and the clinical outcomes were assessed. Progression-free survival (PFS) was estimated using the Kaplan-Meier method and cox regression model was used to conduct multivariate analysis. Fisher’s exact tests were used to calculate clinical benefit. A p value of less than 0.05 was designated as significant (p < 0.05). Results: Chromosome 11q13 amplification (CCND1, FGF3, FGF4, and FGF19) and EGFR mutations were significantly associated with decreased PFS and no clinical benefits after treatment with a programmed death 1 (PD-1) inhibitor. The same results were found in the combined positive score (CPS) ≥ 1 subgroup. In patients who were treated with an EGFR antibody instead of a PD-1 inhibitor, a significant difference in PFS and clinical benefits was only observed between patients with CPS ≥ 1 and CPS < 1. Conclusion: Chromosome 11q13 amplification and EGFR mutations were negatively correlated with anti-PD-1 therapy. These markers may serve as potential predictive biomarkers to identify patients for whom immunotherapy may be unsuitable.